TCSC Penerapan Modul Panel Surya dan Rangkaian Listrik di SD Muhammadiyah 12 Medan Kecamatan, Medan Helvetia - Cholish; Muhammad Rusdi; Faisal Fahmi Hasan; M. Anhar Pulungan; Abdullah; Rischa Devita; Abdul Aziz H; Zarina Binti Ismail (LPPI UMN AL WASHLIYAH, 2025)
The implementation of community service carried out by vocational colleges certainly refers to the application of existing community skills in the educational environment. Increased knowledge and skills can be followed by an increase in the competitiveness of an educational institution. The implementation of the Solar Panel Module learning system and the basic introduction of electrical circuits will spur the development of learning systems through development of technology and information. Training with the application of the Solar Panel Module design method and the basic practice module of electrical circuits can answer the problems that exist in partners. The Collaborative Community Service Training that will be held is expected to establish a good relationship between the TCSC team of Medan State Polytechnic by involving institutions from other universities at home and abroad and Muhammadiyah 12 Elementary School Medan as a fostered partner by establishing an electrical engineering extracurricular activity at the elementary school level that can compete with other schools. The implementation of the training and learning methods is conducted in several stages. Firstly, a survey of activity implementation is conducted to build joint commitment with partners. This is followed by transferring knowledge gained from the Solar Panel Module training, which ultimately prepares for the establishment of a technology-based electrical engineering extracurricular activity tailored to the elementary school level.